ANALISIS KORESPONDENSI HUBUNGAN ANTARA JUMLAH SEKOLAH, JUMLAH SISWA, ROMBEL, JUMLAH GURU, DAN JUMLAH KELAS TERHADAP AKREDITASI SMP SELURUH KECAMATAN KOTA SURABAYA - Suryaningtyas, Wahyuni; Oryza Aprilia Nuril Amin (BESTARI BPS Kalimantan Timur, 2024)
The research was conducted to analyze the relationship between the number of schools, the number of students, the number of study groups (rombel), the number of teachers, and the number of classes on the accreditation of Junior High Schools (SMP) in all sub-districts in the city of Surabaya. The research methodology uses a quantitative approach with correspondence analysis. Correspondence analysis is a multivariate technique that uses visual graphs to see the relationship (closeness) between variables. The data used is secondary data obtained from access to the Dapodik website, the Directorate General of Early Childhood Education, Primary Education and Secondary Education from the Ministry of Education, Culture, Research and Technology, and a case study in the Surabaya city area. Data accessed in May of the even academic year 2023/2024. Analysis using the SPSS data processing application Cross tabulation test data and multi-way correspondence analysis. The results of the analysis of the independence test of the research variables using chi-square show that all hypotheses reject H0, meaning there is a significant relationship between the characteristic variables of junior high school accreditation in all sub-districts of the city of Surabaya. Correlation analysis of the transformed variables shows that the accreditation of Surabaya city sub-district junior high schools has a "Very Strong" relationship with the number of students (0.827); Rombel (0.853); and number of classes (0.877).